LITERATURE REVIEW : EFEKTIVITAS SENAM HAMIL TERHADAP PENURUNAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III - Nura Ida, Salsabila (Sinar : Jurnal Kebidanan, 2025)
ABSTRACT Objective: Back pain is one of the discomforts often experienced by pregnant women, especially in the third trimester. The causative factors include changes in body posture, weight gain, and stretching of ligaments due to fetal growth. Prenatal exercise is believed to help reduce back pain by improving flexibility, balance, and muscle strength of pregnant women. To examine the effectiveness of prenatal exercise in reducing back pain in pregnant women in the third trimester through a literature review of various previous studies. Methods: This Literature Review research was conducted through articles with a database search published by Google Scholar. Results: Based on the results of journal analysis through the Inclusion and Exclusion criteria, thirty journals were obtained that explained the effectiveness of prenatal exercise in reducing pain in pregnant women in the third trimester. Conclusion: Based on the results of all the journals studied, it was stated that six pregnant women were proven to be effective in reducing back pain in pregnant women in the third trimester. By doing prenatal exercise regularly and with the correct technique, pregnant women can feel significant benefits in reducing back pain and improving well-being during pregnancy.